Gender Differences in the Link between Income and Trust Levels: Evidence from Longitudinal Data - Jessica R. Bilson; Michael Jetter; Ingebjørg Kristoffersen (Institute of Labor Economics (IZA), 2017)
We investigate the effect of individual income on interpersonal trust levels, using longitudinal survey data for 22,219 Australians over the 2005-2014 period. Our results produce two key insights. First, we demonstrate the importance of accounting for individual-level fixed effects, as the income coefficient goes from positive and statistically significant in a pooled regression to negative and statistically significant in a fixed effects panel model. Second, this negative effect of income on trust holds only for men, and not for women. This result appears to be concentrated among males who are young and moving from no income to positive income, but employment status is not the driving factor. Further, we explore a potential channel via psychological characteristics and find evidence of men reporting greater levels of neuroticism and fretfulness following an increase in income but, again, women do not. In turn, neuroticism and fretfulness are robust predictors of decreased trust levels; these additional findings are based on cross-sectional variation only, since both these variables are available in only one of the survey waves to date.
Keywords: D01; D31; J16; Z10; 330; gender differences; income levels and trust; interpersonal trust; neuroticism